Water-saving through gravity based Favarra system in the hilly region of Uttarakhand - Kumar, Utkarsh; Kumar, Jitendra; Singh, Sher; Bisht, J K; Kant, Lakshmi (Indian Farming, 2021)
Water scarcity in mountain agriculture is increasing due to climate change, rapid urban expansion, deforestation, forest fires and adverse topographical characteristics. The water availability for agriculture during the lean period (March-June) is a serious challenge to the farmers of hills. In this context efficient utilization of stored rain-water during monsoon season and water harvested from spring may play an important role in combating the water scarcity during the lean season. Due to adverse undulating topography, water application to small size terrace field in hills is a challenging task. In the present study, gravity based low cost favarra system was installed at farmers field to evaluate water saving efficiency compared to traditional irrigation system (syphoning) under the Scheduled Caste Sub-Plan (SCSP) programme of ICAR-Vivekananda Parvatiya Krishi Anusandhan Sansthan, Almora, Uttarakhand. The result showed that water productivity is increased from 33 to 46% by adopting gravity based low cost sprinkler in comparison to traditional syphon system in the hilly region. Therefore, gravity based low cost sprinkler can be used for irrigation on a highly sloping topography.